Blue chicken [videorecording (DVD)] - Freedman, Deborah (Deborah Jane), 1960-; Berneis, Susie (Dreamscape Media, LLC, 2015)
A chicken wreaks havoc in a farmyard with a pot of blue paint.-- The innocent chicken just wants to help, but things get worse and worse, and bluer and bluer, the more she tries. Playing with colors and perspective, and using minimal text, this richly layered story reveals new things to see and laugh about with each reading.